2021
DOI: 10.3390/ijms22094401
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylserine Supplementation as a Novel Strategy for Reducing Myocardial Infarct Size and Preventing Adverse Left Ventricular Remodeling

Abstract: Phosphatidylserines are known to sustain skeletal muscle activity during intense activity or hypoxic conditions, as well as preserve neurocognitive function in older patients. Our previous studies pointed out a potential cardioprotective role of phosphatidylserine in heart ischemia. Therefore, we investigated the effects of phosphatidylserine oral supplementation in a mouse model of acute myocardial infarction (AMI). We found out that phosphatidylserine increases, significantly, the cardiomyocyte survival by 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 73 publications
1
9
0
Order By: Relevance
“…It is well known that some factors, such as advanced age, IS, and LVEF, have been recognized as risk factors for poor outcomes after AMI [ 25 27 ], our results affirmed these conclusions. In epidemiology, the proportion of ALVR after MI in females is higher than in males, and what's more, people with advanced age (female > 65; male > 50) have a high possibility in developing ALVR after MI [ 26 – 28 ].…”
Section: Discussionsupporting
confidence: 88%
“…It is well known that some factors, such as advanced age, IS, and LVEF, have been recognized as risk factors for poor outcomes after AMI [ 25 27 ], our results affirmed these conclusions. In epidemiology, the proportion of ALVR after MI in females is higher than in males, and what's more, people with advanced age (female > 65; male > 50) have a high possibility in developing ALVR after MI [ 26 – 28 ].…”
Section: Discussionsupporting
confidence: 88%
“…PS is ordinarily asymmetrically localized to the internal layer of the plasma membrane. If activated or injured, cells expose PS to the external leaflet of their plasmalemma and form a pattern that is subsequently recognized by macrophages and antibodies [ 33 ]. PS externalization of cardiomyocytes occurs after a short ischemic insult in a rabbit model and is associated with apoptosis [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have pointed out a potential cardioprotective role of phosphatidylserine in heart ischemia [ 70 73 ], suggesting that the phosphatidylserine signaling pathway is associated with MIRI. Schumacher et al [ 74 ] indicated that phosphatidylserine significantly reduced the infarct size by 30% and improved heart function by 25% in a chronic model of acute myocardial infarction (AMI), suggesting that phosphatidylserine supplementation may be a promising novel strategy to reduce infarct size following AMI and to prevent myocardial injury during myocardial infarction or cardiac surgery. A large number of studies have confirmed that chemokines [ 75 77 ], including C-X-C motif chemokine receptor 3 (CXCR3) [ 78 ], are closely related to the ischemia–reperfusion injury.…”
Section: Discussionmentioning
confidence: 99%